The Core Role of Neutrophil–Lymphocyte Ratio to Predict All-Cause and Cardiovascular Mortality: A Research of the 2005–2014 National Health and Nutrition Examination Survey - Gu, Linguo; Xia, Zhenkun; Qing, Bei; Chen, Hongzuo; Wang, Wei; Chen, Ying; Yuan, Yunchang (Frontiers in Cardiovascular Medicine, 2022)
Objective: To further supplement the previous research on the relationship between Neutrophil-Lymphocyte Ratio (NLR) and all-cause or cardiovascular mortality, and construct clinical models to predict mortality. Methods: A total number of 2827 observers were included from the National Health and Nutrition Examination Survey (NHANES) database in our research. NLR was calculated from complete blood count (CBC). According to the quartile of baseline NLR, those observers were divided into four groups. A multivariate weighted Cox regression model was used to analyze the association of NLR and mortality. We constructed simple clinical prognosis models by nomograms. Kaplan-Meier survival curves were used to depict cause-specific mortality. Restricted cubic spline regression was used to make explicit relationships between NLR and mortality. Results: This study recruited 2827 subjects aged ≥ 18 years from 2005 to 2014. The average age of these observers was 51.55±17.62, and 57.69% were male. NLR is still an independent predictor, adjusted for age, gender, race, drinking, smoking, dyslipidemia, and other laboratory covariates. The area under the ROC curves (AUCs) of NLR for predicting all-cause mortality and cardiovascular mortality were 0.632(0.599,0.664) and 0.653(0.581,0.725), which were superior to CRP (AUCs:0.609 and 0.533), and WBC (AUCs:0.522 and 0.513). The calibration and discrimination of the nomograms were validated by calibration plots and C-index, and the C-index (95% CIs) of nomograms for all-cause and cardiovascular mortality were 0.839(0.819,0.859) and 0.877(0.844,0.910). The restricted cubic spline showed a non-linear relationship between NLR and mortality. NLR>2.053 might be a risk factor for mortality. Conclusion: There is a non-linear relationship between NLR and mortality. NLR is an independent factor related to mortality, and NLR>2.053 will be a risk factor for prognosis. NLR and nomogram should be promoted to medical use for practicality and convenience